2013
DOI: 10.1007/s10616-012-9520-8
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumor activity of reversine combined with aspirin in cervical carcinoma in vitro and in vivo

Abstract: A recent report showed that reversine treatment could induce murine myoblasts dedifferentiation into multipotent progenitor cells and inhibit proliferation of some tumors, and other reports showed that apoptosis of lung adenocarcinoma cells could be induced by aspirin. The aim of the present study was to evaluate the synergistic antitumor effects of reversine and aspirin on cervical cancer. The inhibition rate of reversine and aspirin on cervical cancer cell lines' (HeLa and U14) was determined by MTT method, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
13
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
(41 reference statements)
5
13
0
1
Order By: Relevance
“…The anti-tumor behavior of reversine has also been demonstrated in multiple cancers including of melanoma, oral cancer, breast cancer, thyroid cancer, colon cancer, cervical cancer, etc. [ 5 , 7 9 , 11 , 14 , 15 ], and our findings in this study are similar with these reports. The IC50 of reversine in the reported cancer cells are 1 to 20 μM.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The anti-tumor behavior of reversine has also been demonstrated in multiple cancers including of melanoma, oral cancer, breast cancer, thyroid cancer, colon cancer, cervical cancer, etc. [ 5 , 7 9 , 11 , 14 , 15 ], and our findings in this study are similar with these reports. The IC50 of reversine in the reported cancer cells are 1 to 20 μM.…”
Section: Discussionsupporting
confidence: 93%
“…The induction of apoptosis by reversine has been reported in several human tumors [ 7 , 9 , 11 , 14 , 15 ]. However, this is the first time to observe the induction of apoptosis by reversine in human NSCLS cells.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Lloyd et al reported that aspirin suppresses cell adhesion and cell motility in the prostate cancer cell line PC-3 [ 50 ]. Lastly, aspirin treatment decreased the invasiveness of the human cervical cancer cell line Hela [ 51 ]. Although these properties are hallmarks of cancer, none of these studies show an association with mutant PIK3CA status, as all of these cell lines only carry wild-type PIK3CA, with the exception of MCF-7.…”
Section: Discussionmentioning
confidence: 99%
“…Reversine is a synthetic purine that was originally discovered capable of dedifferentiating murine myoblasts to regain multipotency 55 . It has recently been found to possess antitumor capabilities, the exact mechanisms of which have not been clearly defined 8 , 56 , 57 , 58 , 59 , 60 , 61 , 62 . The structural analogy of reversine to ATP implies its major function as a kinase inhibitor 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In vivo , reversine was shown to mildly inhibit multiple myeloma growth in a mouse model with intravenous injection of tumor cells, but not with subcutaneous inoculation, indicating a role of the native bone marrow stromal environment in reversine-induced anti-myeloma activities 8 . Two more recent studies demonstrated that reversine inhibited subcutaneous human cervical and thyroid cancer cell growth in nude mouse models 61 , 62 . Interestingly, both reports showed a mild, delayed tumor growth inhibition by reversine compared to DMSO treatments, with onsets of inhibition between 19 and 40 days after implantation, similar to the growth dynamics in the current study.…”
Section: Discussionmentioning
confidence: 99%